2012
DOI: 10.1039/c2cc17675k
|View full text |Cite
|
Sign up to set email alerts
|

Silver atom and strand numbers in fluorescent and dark Ag:DNAs

Abstract: We use tandem HPLC-mass spectrometry with in-line spectroscopy to identify silver atom numbers, N(Ag), of 10 to 21 in visible- to infrared-emitting Ag:DNA complexes stabilized by oligonucleotide monomers and dimers. Qualitatively different absorbance spectra from bare, same-N(Ag) silver clusters point to silver-base interactions as the origin for the color of Ag:DNAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
193
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(210 citation statements)
references
References 24 publications
(14 reference statements)
16
193
1
Order By: Relevance
“…The second HPLC round used 1,1,1,3,3,3 hexafluoro-2-propanol/triethylamine as the ion-pairing agent to ensure sufficient ionization rates for high sensitivity MS. 32 MS confirms that the cluster stabilized by the modified Ag 15 -DNA host strand contains 15 silver atoms ( Figure S4, Supporting Information). The eluting Ag 15 -DNA is estimated to be g70 ( 1% pure.…”
Section: Resultssupporting
confidence: 75%
“…The second HPLC round used 1,1,1,3,3,3 hexafluoro-2-propanol/triethylamine as the ion-pairing agent to ensure sufficient ionization rates for high sensitivity MS. 32 MS confirms that the cluster stabilized by the modified Ag 15 -DNA host strand contains 15 silver atoms ( Figure S4, Supporting Information). The eluting Ag 15 -DNA is estimated to be g70 ( 1% pure.…”
Section: Resultssupporting
confidence: 75%
“…Recent studies have identified dimeric strand-cluster conjugates by electrospray ionization mass spectrometry. 63 While droplet evaporation might promote strand association through solute concentration, our studies indicate that such species are stable in dilute solution conditions.…”
Section: Discussionmentioning
confidence: 74%
“…Recent mass spectral studies have also identified cluster-DNA conjugates with similar amounts of silver. 63 …”
Section: Resultsmentioning
confidence: 99%
“…20 74,75 Analogously, reduced silver clusters with near-infrared absorption and emission cross-link two cytosine-rich strands and form intermolecular dimers in dilute solutions with 500 nM oligonucleotide concentrations. 31,76,77 On the other hand, DNA strands mold their silver cluster adducts. The nucleobases anchor silver clusters, and cytosine forms the strongest complexes.…”
Section: ■ Discussionmentioning
confidence: 99%